Exendin-4 Potentiates Insulinotropic Action Partly via Increasing β-Cell Proliferation and Neogenesis and Decreasing Apoptosis in Association With the Attenuation of Endoplasmic Reticulum Stress in Islets of Diabetic Rats - Dae Young Kwon; Young Sup Kim; Il Sung Ahn; Da Sol Kim; Suna Kang; Snag Mee Hong; Sunmin Park (Elsevier, 2009)
Exendin-4, a long-acting glucagon-like peptide-1-receptor agonist, is known to enhance β-cell function, but the active mechanism by which it modulates β-cell mass still remains unclear. We investigated what the long-term effects of exendin-4 (300 pmol/kg body weight per day) on β-cell function and mass would be in 90% pancreatectomized (Px) Sprague Dawley rats; half of whom were intraperitoneally injected with streptozotocin (STZ, 20 mg/kg body weight) and half of whom were not. Exendin-4 improved glucose tolerance by elevating serum insulin levels in both STZ-treated and untreated Px rats. At hyperglycemic clamp, STZ attenuated both first and second phase insulin secretion in STZ- and saline-treated Px rats, but exendin-4 incompletely reversed the attenuation. Since STZ mostly removed the remaining β-cells by increasing apoptosis after Px, their regeneration was initiated through neogenesis, which was determined by the number of β-cells budding from pancreatic duct layers and small clusters. Exendin-4 enhanced β-cell proliferation and neogenesis in STZ-treated and -untreated Px rats and reduced β-cell apoptosis partly by attenuating the expression of endoplasmic reticulum stress-response genes such as X-box-binding protein-1, activating transcription factor (ATF)-4, ATF6, and C/EBP-homologous protein. In conclusion, exendin-4 improved glycemic control by potentiating β-cell function and increasing β-cell mass by increasing β-cell neogenesis and proliferation and by decreasing apoptosis in diabetic rats. Keywords:: insulin secretion, β-cell mass, streptozotocin, apoptosis, endoplasmic reticulum stress